Iowa CBC reporting form, Muscatine, December 29, 1985 - Petersen, Peter C.et al (1985)
Checklist dated December 29, 1985 compiled by Peter Petersen. A list of birds sighted by Petersen and fifteen others around Muscatine. A total of 58 species and 7,647 individual birds were sighted. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Winter 1985-1986. Epson - sheet feed